ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PRILAKU WAJIB PAJAK ORANG PRIBADI DALAM MELAPORKAN SPT MENGGUNAKAN E-FILING WAJIB PAJAK ORANG PRIBADI KOTA DOMPU - Desi Puji Astuti; Nur Diana; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACT Responding and answering related to the increasing needs of taxpayers throughout Indonesia by improving services must be better than before and there is a desire to reduce the burden of the administration process of taxation reports using paper. One of the tax renewals in terms of the use of Information Technology (IT) for tax administration is implementing electronic media in the form of E-Systems namely E-Filling. This study analyzes the Analysis of Factors Affecting Personal Taxpayer Behavior Interest in Reporting Tax Returns Using E-Filling. The variables used in this study are perceived usefulness, readiness of information technology, security and confidentiality, and perceived convenience as an independent variable, while the dependent variable is interest in using E-Filling. In this study there were 95 respondents used. The results of this study that simultaneously the variable Usage Perception, Information Technology Readiness, Security and Confidentiality, and Ease Perception simultaneously affect the Interest in E-Filling Use. While partially the variable Perception of Use has a positive and significant effect on the Interest in Using E-filling, so the readiness of information technology has a positive effect on the interest in using E-filling, the Security and Confidentiality variable has no influence on the Interest in Using E-Filling, the Perception of Ease variable has no effect of Interest in Using E-Filling.Keywords: perception of use, readiness of information technology, security and confidentiality, perceived ease of use, and interest of E-Filling users.